Resistance of Bt-maize (MON810) against the stem borers Busseola fusca (Fuller) and Chilo partellus (Swinhoe) and its yield performance in Kenya. (November 2016) - Tefera, Tadele; Mugo, Stephen; Mwimali, Murenga; Anani, Bruce; Tende, Regina; Beyene, Yoseph; Gichuki, Simon; Oikeh, Sylvester O.; Nang'ayo, Francis; Okeno, James; Njeru, Evans; Pillay, Kiru; et al.
Abstract: A study was conducted to assess the performance of maize hybrids with Bt event MON810 ( Bt -hybrids) against the maize stem borer Busseola fusca (Fuller) in a biosafety greenhouse (BGH) and against the spotted stem borer Chilo partellus (Swinhoe) under confined field trials (CFT) in Kenya for three seasons during 2013–2014. The study comprised 14 non-commercialized hybrids (seven pairs of near-isogenic Bt and non- Bt hybrids) and four non-Bt commercial hybrids. Each plant was artificially infested twice with 10 first instar larvae. In CFT, plants were infested with C. partellus 14 and 24 days after planting; in BGH, plants were infested with B. fusca 21 and 31 days after planting. In CFT, the seven Bt hybrids significantly differed from their non-Bt counterparts for leaf damage, number of exit holes, percent tunnel length, and grain yield. When averaged over three seasons, Bt -hybrids gave the highest grain yield (9.7 t ha −1 ), followed by non- Bt hybrids (6.9 t ha −1 ) and commercial checks (6 t ha −1 ). Bt -hybrids had the least number of exit holes and percent tunnel length in all the seasons as compared to the non- Bt hybrids and commercial checks. In BGH trials, Bt -hybrids consistently suffered less leaf damage than their non-Bt near isolines. The study demonstrated that MON810 was effective in controlling B. fusca and C. partellus . Bt -maize, therefore, has great potential to reduce the risk of maize grain losses in Africa due to stem borers, and will enable the smallholder farmers to produce high-quality grain with increased yield, reduced insecticide inputs, and improved food security. Highlights: The present trials were conducted to generate empirical information for commercialization of Bt-maize in Kenya. This study reports on the efficacy of Bt maize (MON810) against the tem borers, Busseola fusca and Chilo partellus in Kenya. Bt- maize significantly reduced leaf damage, number of exit holes, percent tunnel length, and increased grain yield.